Damage study and seismic vulnerability assessment of existing masonry buildings in Northeast India. (May 2020) - Halder, Lipika; Chandra Dutta, Sekhar; Sharma, Richi Prasad
Abstract: The Northeast region of India is considered to be the most seismically active zone in India, having witnessed two major earthquakes ( M w > 8) in the past. Recently, the 2017 Ambasa earthquake (with M w of 5.7) caused significant damage to unreinforced masonry (URM) buildings in Tripura, a Northeast state of India. The typical nature of damage observed in URM buildings during the post-earthquake damage survey highlights poor construction practices that have been used in this region even though the seismic hazard of the Northeast region of India is well established. In this context, the present study is an effort to evaluate through fragility analysis the vulnerability of existing low-rise URM buildings in Agartala, the capital city of Tripura, which in a broader sense represents the buildings of the entire Northeast region of India, through fragility analysis. In this regard, an assessment method based on a nonlinear static approach is used to develop bilinear capacity curve parameters. The capacity curve parameters are then used to estimate fragility functions. Fragility analysis shows that URM buildings would suffer heavy damage even for an earthquake having Peak Ground Acceleration (PGA) of 0.18 g, which is used to design buildings in the Northeast region of India according to the Indian seismic code. Fragility curves developed in this study may prove useful for assessing the seismic risk of the same building typology in other urban areas of Northeast India. In this first attempt, however, the effect of variability from construction quality and modelling uncertainty on the fragility curves is not considered in the limited scope of the present study. Highlights: Low-rise URM buildings, which greatly increase the seismic risk of any area are frequently observed in Northeast India. A moderate earthquake ( M w 5.7) caused considerable damage to URM buildings in Tripura, a Northeast state of India. To assess the seismic vulnerability of low-rise URM buildings, fragility analysis is carried out using bilinear capacity curve parameters. The fragility curves may be used to assess the seismic risk of the same building typology to the other city in Northeast India.